2010
DOI: 10.1186/2041-9414-1-16
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induced genomic instability in nucleotide excision repair-deficient lymphoblastoid cells

Abstract: BackgroundThe Nucleotide Excision Repair (NER) pathway specialises in UV-induced DNA damage repair. Inherited defects in the NER can predispose individuals to Xeroderma Pigmentosum (XP). UV-induced DNA damage cannot account for the manifestation of XP in organ systems not directly exposed to sunlight. While the NER has recently been implicated in the repair of oxidative DNA lesions, it is not well characterised. Therefore we sought to investigate the role of NER factors Xeroderma Pigmentosum A (XPA), XPB and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
0
18
0
1
Order By: Relevance
“…Recently, Martino and colleagues (2011) found that intracellular hydrogen peroxide production in cancer cells and artery endothelial cells was suppressed in the HMF [36]. Reactive oxygen species, especially hydrogen peroxide, has been reported to induce genomic instability in mammalian cells [37], [38]. Thus, further investigation into the changes in genetic material and intracellular reactive oxygen species levels during HMF exposure would be of value.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Martino and colleagues (2011) found that intracellular hydrogen peroxide production in cancer cells and artery endothelial cells was suppressed in the HMF [36]. Reactive oxygen species, especially hydrogen peroxide, has been reported to induce genomic instability in mammalian cells [37], [38]. Thus, further investigation into the changes in genetic material and intracellular reactive oxygen species levels during HMF exposure would be of value.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above hypothesis, XPB- and XPD-deficient lymphoblastoid cells are hypersensitive to H 2 O 2 and display higher H 2 O 2 -induced DNA damage compared to wild type cells [94]. XPA-deficient cells also display defects in response to oxidative DNA damaging agents, including an increase in H 2 O 2 genotoxicity, a lower threshold for H 2 O 2 -induced cell cycle arrest, and reduced repair of H 2 O 2 generated DNA lesions [95].…”
Section: Oxidative Dna Damage In Human Diseasementioning
confidence: 65%
“…Loss of XPB or XPD increases telomere attrition and enhances DNA damage at telomeres under oxidative stress, suggesting that XPB and XPD may have an important role in maintaining telomere integrity [54, 55]. Another key NER component, XPC, has been implicated in telomere maintenance as well, particularly upon UV exposure.…”
Section: Ner At Telomeresmentioning
confidence: 99%